Exploring Histoplasma species seroprevalence and risk factors for seropositivity in The Gambia’s working equid population: Baseline analysis of the Tackling Histoplasmosis project dataset - Cornell, Tessa Rose; Fye, Biram Laity; Nyassi, Edrisa; Ceesay, Fatou; Jallow, Mahmud; Langendonk, R. Frèdi; Wootton, Dan G.; Pinchbeck, Gina; Scantlebury, Claire Elizabeth (Frontiers in Veterinary Science, 2024)
IntroductionExposure rates to Histoplasma species, the causative agent of equine epizootic lymphangitis (EL), are unknown amongst working equids in The Gambia. The primary aims of this study were to estimate anti-Histoplasma antibody seroprevalence in the equid population in rural The Gambia and to explore risk factors for seropositivity.MethodsA nationwide cross-sectional study was conducted (February–July 2022), representing baseline measurements of a longitudinal cohort study. Horses (n = 463) and donkeys (n = 92) without EL signs were recruited in 18 study sites. Following informed owner consent, equid clinical and management data were recorded. Blood samples were collected by jugular venepuncture, and sera were subject to the IMMY Latex Agglutination Histoplasma test (LAT). Seropositivity risk factors were explored by multi-level, multivariable logistic regression analysis. Study site and household variance were described using a latent-variable approach. Whole blood DNA extractions were subject to nested ITS-PCR to detect Histoplasma capsulatum var. farciminosum (HCF), and agreement with LAT results was measured using Cohen’s kappa statistic.ResultsAnti-Histoplasma antibody seroprevalence in horses and donkeys was 79.9% [95% confidence interval (CI) 76.0–83.5%] and 46.7% (95% CI 36.3–57.4%), respectively. In horses, two multivariable models explained the maximum amount of data variability. Model 1 demonstrated increased odds of seropositivity in mares [odds ratio (OR) = 2.90 95% CI 1.70–4.95, p < 0.001] and decreased odds in horses <2.5 years (OR = 0.46 95% CI 0.22–0.95, p = 0.04; reference: ≥4.5 years). Model 2 demonstrated increased odds in horses recruited during the rainy season (OR = 2.03 95% CI 1.08–3.84, p = 0.03) and those owned by farmers reporting previous EL in their equids (OR = 1.87 95% CI 1.04–3.37, p = 0.04). Decreased odds were measured in horses <2.5 years (OR = 0.37 95% CI 0.18–0.78, p = 0.01) and horses reported to transport firewood (OR = 0.45 95% CI 0.28–0.74, p = 0.001). On multivariable analysis of donkeys, decreased odds of seropositivity were demonstrated amongst donkeys owned by households which also owned horses (OR = 0.23 95% CI 0.06–0.85, p = 0.03). HCF infection prevalence in horses and donkeys was 22.0% (n = 102/463, 95% CI 18.3–26.1%) and 5.4% (n = 5/92, 95% CI 1.8–12.2%), respectively. No significant agreement was measured between LAT and nested ITS-PCR results (κ < 0.00).ConclusionHigh Histoplasma spp. exposure was demonstrated amongst equids in The Gambia. Investigation of risk factors, including equid husbandry and management strategies, as well as geoclimatic variations, is warranted. Outcomes may inform sustainable and equitable EL control strategies in The Gambia and comparable settings worldwide.